Cooperation of Ukraine and Republic of Poland: Economic and Diplomatic Aspects - V. V. Ryeznikov; V. V. Ryeznikov (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Poland in viewed by Ukraine as a reliable economic and political partner supporting Ukraine’s intention to integrate in Europe. Therefore, facts, documents and statistical data reflecting qualitative and quantitative aspects of relations between Ukraine and Poland need to be subject to non-stop monitoring and analysis, to help in finding timely solutions for problematic issues that may occur in these countries’ relations. The article’s objective is to analyze the performance and perspectives of economic and diplomatic relations between Ukraine and Republic of Poland. The analysis of documents on diplomatic and economic cooperation of the two countries after they gained political independence, and statistical data on trade in goods and services (by category) and investment flows (by data on direct investment from Ukraine to Poland and from Poland to Ukraine) shows that both countries have immense potentials for cooperation in various fields. As regards diplomatic dimension, Republic of Poland is the strongest promoter and lobbyist of the Euro-integration and Euro-Atlantic course of Ukraine. Regarding the economic cooperation, while mutual trade in goods declined in 2014 due to the economic and political crisis in Ukraine, it grew in 2016 with the recovery processes in the Ukrainian economy. Mutual trade in services is less intensive than trade in goods. Analysis of the investment cooperation shows the large asymmetry in favor of Polish investors in Ukraine and the reducing investment in both directions in the latest years.